Service Performance Indicator Sebagai Upaya Peningkatan Kualitas Pelayanan Publik di Stasiun Lempuyangan Yogyakarta - Deby Febriyan Eprilianto (Yogyakarta State University, 2013)
This study aims to identify and explain the improvement of the quality of public services through the optimization of transportation policies in Lempuyangan Railway Station Yogyakarta. This study is a descriptive qualitative research and taking place in PT KAI Yogyakarta Region VI Operations and in station Lempuyangan. The results of this study concluded that: (1) improving the quality of public services through the optimization of transport policies in station Lempuyangan Yogyakartathat is based on the Minister of Transportation Regulation Number 09 year 2011 on Minimum Service Standards (MSS) for public transportation by train has been implemented optimally by implementing Service Performance Indicator (SPI) program, which consists of eleven indicators namely : (a) SPI Information, (b) SPI Cleanliness and Health, (c) SPI Ticket Service, (d) SPI Security, (e) SPI staff and Officers, (f) SPI Waiting Room, (g) SPI Public Facilities, (H) SPI Peron, (i) SPI parking, (j) SPI Lighting, and (k) SPI Toilet, and (2) the application of SPM and SPI optimally made Lempuyangan station got third winner in the best station award in 2013.Keywords: Quality Improvement Services, Transportation Policy